Diabetes Attitudes, Wishes and Needs second study (DAWN2™): Cross‐national comparisons on barriers and resources for optimal care—healthcare professional perspective. Issue 7 (23rd June 2013) - Holt, R. I. G.; Nicolucci, A.; Kovacs Burns, K.; Escalante, M.; Forbes, A.; Hermanns, N.; Kalra, S.; Massi‐Benedetti, M.; Mayorov, A.; Menéndez‐Torre, E.; Munro, N.; Skovlund, S. E.; et al.
Abstract Aims The second Diabetes Attitudes, Wishes and Needs (DAWN2) study sought cross‐national comparisons of perceptions on healthcare provision for benchmarking and sharing of clinical practices to improve diabetes care. Methods In total, 4785 healthcare professionals caring for people with diabetes across 17 countries participated in an online survey designed to assess diabetes healthcare provision, self‐management and training. Results Between 61.4 and 92.9% of healthcare professionals felt that people with diabetes needed to improve various self‐management activities; glucose monitoring (range, 29.3–92.1%) had the biggest country difference, with a between‐country variance of 20%. The need for a major improvement in diabetes self‐management education was reported by 60% (26.4–81.4%) of healthcare professionals, with a 12% between‐country variance. Provision of diabetes services differed among countries, with many healthcare professionals indicating that major improvements were needed across a range of areas, including healthcare organization [30.6% (7.4–67.1%)], resources for diabetes prevention [78.8% (60.4–90.5%)], earlier diagnosis and treatment [67.9% (45.0–85.5%)], communication between team members and people with diabetes [56.1% (22.3–85.4%)], specialist nurse availability [63.8% (27.9–90.7%)] and psychological support [62.7% (40.6–79.6%)]. In some countries, up to one third of healthcare professionals reported not having received any formal diabetes training. Societal discrimination against people with diabetes was reported by 32.8% (11.4–79.6%) of participants. Conclusions This survey has highlighted concerns of healthcare professionals relating to diabetes healthcare provision, self‐management and training. Identifying between‐country differences in several areas will allow benchmarking and sharing of clinical practices.